2017
DOI: 10.1038/s41598-017-10683-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the cognitive processes underlying mental rotation: an eye-movement study

Abstract: Mental rotation is an important paradigm for spatial ability. Mental-rotation tasks are assumed to involve five or three sequential cognitive-processing states, though this has not been demonstrated experimentally. Here, we investigated how processing states alternate during mental-rotation tasks. Inference was carried out using an advanced statistical modelling and data-driven approach – a discriminative hidden Markov model (dHMM) trained using eye-movement data obtained from an experiment consisting of two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 44 publications
(45 reference statements)
4
36
0
Order By: Relevance
“…Several previous ERP studies have observed significant differences between upright and inverted stimuli in time periods starting at ~400 ms, an effect that has specifically been attributed to MR 31,35 . However, while these studies suggested a single cognitive component, our segmentation and source analyses support -akin to previous modelling studies 44,45 -at least three distinct processing stages. The first stage (290-360 ms) was represented by Map 6 which was mainly present when rotated hands were manipulated.…”
Section: Discussionsupporting
confidence: 86%
“…Several previous ERP studies have observed significant differences between upright and inverted stimuli in time periods starting at ~400 ms, an effect that has specifically been attributed to MR 31,35 . However, while these studies suggested a single cognitive component, our segmentation and source analyses support -akin to previous modelling studies 44,45 -at least three distinct processing stages. The first stage (290-360 ms) was represented by Map 6 which was mainly present when rotated hands were manipulated.…”
Section: Discussionsupporting
confidence: 86%
“…For the angular disparity of 0°, the perceptual and decision-making stages are separated from the rotation stage as no mental rotation needs to be performed. In this context, the novel gridded AOIs analysis 23 , which showed sex differences only at 0°, suggests that men and women are likely to possess different perceptual (visual search) and decision-making mechanisms, but similar mental rotation processes.…”
Section: Discussionmentioning
confidence: 91%
“…Mental rotation -has "five sequential cognitive-processing stages, perceptual coding of the stimulus, identification of the stimulus and orientation, mental rotation of the stimulus, a judgment of parity, and response and execution". It needs eye movement, maintaining gaze, eye tracking, and fixing the visual information [8]. The mental rotation task has one original image on one side and two or more images on the other side.…”
Section: Digitalized Spatial Games and Their Effects On Cognitionmentioning
confidence: 99%